Efficacy of cats hemotranfusion in anemia: a clinical case - Malyuk, M.; Klymchuk, V.; Kulida, M.; Yegorov, O. (Scientific Progress & Innovations, 2022)
The question of donation in cats and the use of both whole blood and its components remains quite relevant in veterinary practice. Blood transfusion in cats can effectively combat various etiologies of anemia, or at least stabilize the patient for further research and finding solutions to a specific pathology of an individual animal. Steps should be taken to ensure, as far as possible, blood compatibility between donor and recipient cats. At a minimum, the blood type A / B / AB of both cats should be checked, and ideally a further cross-test should be performed to identify Mik antigen and other incompatibilities. Cats, unlike dogs, have natural antibodies (alloantibodies) against a blood group that they lack. Donor cats should be healthy, fully vaccinated, 2−8 years old, weigh more than 4 kg, PCV should be more than 30 % (ideally more than 35 %), do not contain FeLV / FIV / Mycoplasma haemofelis. Donor cats should also be screened for bloodborne infections, including feline leukemia virus (FeLV), feline immunodeficiency virus (FIV) and Mycoplasma haemofelis (the causative agent of infectious anemia in cats). The article describes the clinical case of blood transfusion for anemia in cats and the results of laboratory tests and the effectiveness of treatment measures. The use of whole blood transfusion to the recipient animal makes it possible to increase the number of erythrocytes, hemoglobin content, hematocrit index, which has a positive effect on blood oxygenation, redox processes in the body of the recipient animal, and its general clinical condition. It was established that the clinical condition of an animal with chronic anemia remains satisfactory. Such a phenomenon can be explained by adaptive and compensatory processes that occur in animals with chronic anemia. But the issue of anemia, which did not arise as a result of blood loss, requires a more detailed study in each case and the impact, if possible, on the root cause of its development. After all, in the absence of the latter, the animal's condition and basic hematological parameters will return to baseline, and the patient's recovery, or at least long-term remission, will not be achieved.